More Than Morningness: The Effect of Circadian Rhythm Amplitude and Stability on Resilience, Coping, and Sleep Duration - Di Milia, Lee; Folkard, Simon (Frontiers in Psychology, 2021)
Self-report tools that measure circadian rhythms have focused primarily on phase. We add to the sparse literature on assessing amplitude and stability. We randomly recruited 1163 participants who completed several measures. The correlation between the LV scale (amplitude) and FR scale (stability) was -0.12 (p < 0.01). As expected, amplitude was negatively associated with phase (r = -0.64, p < 0.01) while stability showed a weak link with phase (r = 0.07, p < 0.05). Structural equation modelling suggested a close model-fit of the factor structure in the sample (RMSEA = 0.033). The LV scale explained 22% of the variance, while the FR scale explained 23%. Scale reliability was satisfactory for the LV scale (0.68) and good for the FR scale (0.73). Participants with low amplitude or flexible rhythms reported significantly better resilience, coping, and required less daily sleep. We constructed a composite circadian categorical variable to combine the best attributes from the LV and FR scales; participants with both low amplitude and flexible rhythms, reported significantly better resilience, coping, and less sleep need. We found rhythm amplitude decreased with age, while stability remained constant.